Cotrimoxazole-Resistant Escherichia coli Bacteremia in Neutropenic Patients at a Regional Oncology Hospital. (1992) - Gregson, Daniel B; Matlow, Anne G; Simor, Andrew E; Tuffnell, Peter G; Low, Donald E; Feld, Ronald; Brunton, James E
Abstract : In a regional oncology hospital using cotrimoxazole (trimethoprim-sulphamethoxazole) prophylaxis during chemotherapy-induced neutropenia, a single strain of Escherichia coli (indole negative) caused 15 of 27 episodes of Gram-negative rod bacteremia in 1987, and four of 32 such episodes in 1988. This biotype had not been recovered in 1986. Investigations during this 'outbreak' of bacteremias revealed enteric colonization with this strain of E coli in 37% of patients on leukemia or bone marrow transplant wards and in several staff members in July 1987. In 1988, 11 of 32 Gram-negative rod bacteremias were secondary to other strains of indole positive E coli of several different biotypes and plasmid profiles. Indole negative strains all exhibited low level trimethoprim resistance, whereas indole positive strains which subsequently appeared exhibited high level trimethoprim resistance. Failure of cotrimoxazole prophylaxis was initially due to the clonal dissemination of a single strain of E coli within the institution, with the subsequent appearance of multiple E coli strains with probable differing genetic bases for their resistance.